Observation of Peripapillary Choroidal Vascularity in Natural Disease Course and After Gene Therapy for Leber's Hereditary Optic Neuropathy - Jiang, Jingwen; Sun, Gongpeng; Miao, Qingmei; Li, Bin; Wang, Dan; Yuan, Jiajia; Chen, Changzheng (Frontiers in Medicine, 2021)
PURPOSE To compare peripapillary choroidal vascularity among Leber’s Hereditary Optic Neuropathy (LHON) patients at different stages of natural course and healthy controls using optical coherence tomography (OCT), and to evaluate peripapillary choroidal vascularity changes in LHON patients before and after gene therapy. METHODS 57 LHON patients and 15 healthy controls were enrolled in this prospective clinical study. LHON patients were divided into three duration groups based on stage of disease progression. Both patients and healthy controls underwent OCT scans focused on the optic disc at baseline with Heidelberg Spectralis, and patients underwent OCT at 1, 3, and 6 months after gene therapy. OCT images were converted and binarized using ImageJ software. Choroidal thickness (CT), total choroidal area (TCA), and choroidal vascularity index (CVI) in each quadrant of OCT images were measured to evaluate peripapillary choroidal vascularity. RESULTS At baseline, the average CT was not significantly different between LHON patients at different stages and between healthy controls (P=0.468). Although average TCA and average CVI were slightly higher in LHON patients at different stages than in healthy controls, the difference was not statistically significant (P =0.282 and 0.812, respectively). After gene therapy, The average TCA at 1 month after gene therapy was significantly higher than that before gene therapy (P = 0.003)，while no significant differences were found in the average CT or average CVI in LHON patients before and 1,3 and 6 months after gene therapy using pairwise comparisons (all P > 0.05). CONCLUSIONS No significant difference was found in choroidal vascularity of LHON patients at different stages and healthy controls. Choroidal vascularity seems to stay stable after gene therapy.